On the prudence of adopting a ‘sin now; repent later’ policy - Mawson, TJ (Cambridge University Press, 2023)
‘Listen, I'm against sin. I'll kick it as long as I've got a foot; I'll punch it as long as I've got a fist; I'll butt it as long as I've got a head; and I'll bite it as long as I've got a tooth’ (Billy Sunday). Billy Sunday was a revivalist preacher in the early half of the twentieth century. I take it that Billy's approach to sin will be taken by most to be more theologically acceptable than the following. ‘I figure I'll go for the life of sin, followed by the presto-change-o deathbed repentance’ (Bart Simpson). Bart Simpson is a character in the animated TV Show, The Simpsons. In the vignette from which this quotation of Bart's is abstracted, Bart is actually in conversation with a Billy-Sunday-like preacher. The preacher, on hearing of Bart's theology (Bartian theology, we may call it; not, NB Barthian theology), replies in a slightly stunned way, as if he had never himself considered Bartianism prior to that particular moment, ‘Wow! That is a good angle. . .’ However, he quickly collects himself and adds definitively, ‘But it's not God's angle.’ In this article, I wish to explore Bart's angle; could it, or something like it, after all, be a prudent angle?